PENGGUNAAN APLIKASI GOOGLE MEET SEBAGAI MEDIA PERKULIAHAN DARING - Ratna Lusia Boru Sirait; Dona Fitriawan; Yulis Jamiah; Sugiatno Sugiatno; R Zubaidah; Agung Hartoyo (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2023)
The rapid spread of the Covid-19 infection requires all learning to switch from face-to-face learning to online learning to break the chain of infection transmission. This learning does not fully run smoothly due to limitations and the availability of supporting media. Not all educators and students have an understanding of using internet media. only google meet is fast to use for distance learning. The Google Meet application provides features that support the implementation of bold learning, is free and uses web quota that is more efficient or more stable. Which aims to be a place for learning that is carried out online learning during the covid. This of course makes it easier for students (students and students) to access Google Meet compared to other media platforms. This study aims to determine the effectiveness of using Google Meet as a learning medium during the Covid-19 pandemic. The method used is a qualitative method, namely by obtaining an in-depth understanding, developing theory, describing how the Google Meet application works. The data collected beforehand was directly in class, while the case of Covid 19 could not collect data directly. Research shows that Google Meet was very effective in being used in the teaching process during the Covid 19 period, because it was very easy to access and there was no need to pay and can be used anywhere and anytime.